(untitled) (SAARC Journal of Agriculture, 2022)
Cauliflower (Brassica oleracea var. botrytis L.) is one of the most popular vegetable crops. An experiment was conducted to study the response of late season varieties of cauliflower to different sources of nitrogen on growth, yield and postharvest quality at Rampur, Chitwan, Nepal during October 2018 to March 2019. Four late season varieties of cauliflower viz. NS 106, Snow Moon, Yukon, and Candid Charm and three different sources of nitrogen viz. 100% Nitrogen (N) through Farm yard manure, 50% N through FYM and 50% N through urea, and 100% N through urea. The two-factor experiment was laid in RCBD with three replications and twelve treatment combinations. All the recorded growth, yield and postharvest quality parameters were significantly higher and statistically similar in NS 106 and Yukon and significantly lower in Candid Charm. Similarly, significantly higher plant height, canopy diameter, leaf number, curd height, economic yield and biological yield were recorded in 50% N through FYM and 50% N through urea. Significantly lower plant height, canopy diameter, leaf number, economic yield and biological yield, titrable acidity and significantly higher days to curd maturity, vitamin C and dry matter content of leaf and curd, and TSS content were recorded in 100% N through FYM. Results revealed that for higher and postharvest quality of cauliflower during late season at Rampur, Chitwan Yukon or NS 106 both varieties were superior along with 50% N through FYM and 50% N than those of the other varieties. SAARC J. Agric., 19(2): 195-205 (2021)